Facebook Recruitment for Children with Advanced Cancer and Their Parents: Lessons from a Web-based Pediatric Palliative Intervention Study. (3rd September 2021) - Cho, Eunji; Gilmer, Mary Jo; Friedman, Debra L.; Hendricks-Ferguson, Verna L.; Hinds, Pamela S.; Akard, Terrah Foster
Abstract : Participant recruitment for pediatric palliative intervention studies is a chronic challenge for researchers. Digital recruitment strategies, or digital technology-assisted recruitment methods used to remotely reach and enroll research subjects, can help address these recruitment challenges for pediatric palliative care clinical trials. This study (a) describes Facebook recruitment procedures targeting children with cancer and their parents for a pediatric palliative intervention randomized clinical trial, (b) reports recruitment results, and (c) discusses successful strategies to recruit pediatric populations via Facebook advertisements. Researchers used Facebook advertisements to recruit children with advanced cancer (aged 7–17 years) for a web-based legacy intervention. Between years 2015 and 2018, our research team enrolled 150 child–parent dyads (N = 300) to participate in the web-based legacy program. Results suggest that Facebook advertisements can be a successful tool to access and recruit pediatric populations with life-threatening conditions. Further research is needed to determine how innovative social-media recruitment strategies could be used in other populations of patients with serious illnesses and their caregivers to further advance the science in palliative care.